2005
DOI: 10.1128/jb.187.11.3807-3813.2005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Turnover Element in Region 2.1 of Escherichia coli σ 32 by a Bacterial One-Hybrid Approach

Abstract: Induction of the heat shock response in Escherichia coli requires the alternative sigma factor 32 (RpoH). The cellular concentration of 32 is controlled by proteolysis involving FtsH, other proteases, and the DnaKJ chaperone system. To identify individual 32 residues critical for degradation, we used a recently developed bacterial one-hybrid system and screened for stabilized versions of 32 . The five single point mutations that rendered the sigma factor more stable mapped to positions L47, A50, and I54 in reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 31 publications
5
53
0
Order By: Relevance
“…The predicted three-dimensional structure suggested that amino acids at positions 47, 50 and 54 are positioned on the same side of the putative ahelix 12a in region 2.1 of RpoH (Obrist & Narberhaus, 2005). The sequence of region 2.1 from 21 bacterial species shows that several RpoH proteins contain a proline residue at position 47 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The predicted three-dimensional structure suggested that amino acids at positions 47, 50 and 54 are positioned on the same side of the putative ahelix 12a in region 2.1 of RpoH (Obrist & Narberhaus, 2005). The sequence of region 2.1 from 21 bacterial species shows that several RpoH proteins contain a proline residue at position 47 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additional point mutations in region 2.1 that render E. coli RpoH more active in vivo Point mutations in RpoH region 2.1 at positions 47, 50, 51, 54 or 55 were shown to turn the sigma factor into a stabilized protein, resulting in enhanced transcription of an RpoH-dependent promoter in vivo (Horikoshi et al, 2004;Obrist & Narberhaus, 2005). The predicted three-dimensional structure suggested that amino acids at positions 47, 50 and 54 are positioned on the same side of the putative ahelix 12a in region 2.1 of RpoH (Obrist & Narberhaus, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations